(untitled) (Jurnal Ilmu Komputer dan Sistem Informasi, 2014)
Social networks are everywhere: our email and phone books, our family relatives, and our business connections, all define either explicit or implicit social networks. Social networks have existed long before the Internet, but their recent web-based form, as exhibited by companies like Facebook and Twitter, made them more tangible. In their new manifestation, social networks have become attractive playground for viral marketing: the dream of any marketer is that a products will be promoted via “word to mouth” (which relies on social networks). In order to make that dream a reality, various forms of marketing have been advocated. That called affiliate marketing, direct marketing, and multi-level-marketing all refer to (overlapping) approaches that facilitate viral marketing. In this paper, we shall adhere to the term multi level marketing as it seems to be the least restrictive one. Key words Web-based multi-level-marketing, SDLC (System Development Life Cycle).